Diagnóstico de las áreas administrativa, financiera, comercial y operativa de las microempresas Reciplas Armenia, Fábrica de Resortes y Repuestos Materon, Hacienda Pisamal, Taller de Mecánica y Star Pizza del Eje Cafetero, afiliadas a la Cooperativa de Ahorro y Crédito Cofincafe a 2013 del municipio de Armenia. (2014)
The present project aims to conduct a study to each of the areas of micro-enterprises Reciplas Armenia, Fábrica de Resortes y Repuestos Materon, Hacienda Pisamal, Taller de Mecánica, and Star Pizza of Eje Cafetero, affiliated to the cooperative credit and savings COFINCAFE of the municipality of Armenia to 2013, in order to know their current status, and make a diagnosis, that it will be possible to identify weaknesses and shortcomings that impede its continuous improvement, as well as the opportunities that may become potential aspects for its economic growth. Then of having analyzed the information and found results arise an improvement plan, where are established each of the actions and strategies needed to strengthen the weaknesses that currently facing microenterprise.